PENGARUH PROMOSI DAN KEPERCAYAAN KONSUMEN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA APLIKASI SHOPEE (STUDI PADA MAHASISWA STIE PELITA NUSANTARA SEMARANG) - Ummi, Riadatul; Widodo, Untung (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
The purpose of this study was to determine the effect of Promotion and Consumer Trust on Customer Satisfaction as an intervening variable in the shopee application, and to determine the effect of Promotion, Consumer Trust, and Customer Satisfaction on Customer Loyalty. The research method used in this research is Path Analysis. The population of this research is the consumers of Stie Pelita Nusantara Semarang students. The sample of this study was 120 people using a non-probability sampling technique with a purposive sampling approach, namely the researcher chose a purposive sample subjectively. The data collection method is by distributing questionnaires via the Google form. The type of data used is primary data. The results of this study indicate that Promotion has an effect on Customer Satisfaction and Consumer Trust has an effect on Customer Satisfaction. Promotion has no effect on Customer Loyalty, while Consumer Trust has no effect on Customer Loyalty. Promotion and Consumer Trust have an effect on Customer Loyalty with Customer Satisfaction as an intervening variable in the shopee application. Keywords: Promotion, Consumer Trust, Customer Satisfaction, and Customer Loyalty.